In this article, from different sides considered the idea of the theoretical value that the power is given by God and to understand that the historical process is the scourge of fate and that God’s will is done in the traditional political culture of Japa - Тургенбaй A.А.,, A. А.; Орaзбековa Г.Р., Г. Р. (Journal of Oriental Studies, 2017)
In this article, from different sides considered the idea of the theoretical value that the power is given by God and to understand that the historical process is the scourge of fate and that God’s will is done in the traditional political culture of Japan.